2020
DOI: 10.1186/s13052-020-0814-8
|View full text |Cite
|
Sign up to set email alerts
|

Dieulafoy lesion: two pediatric case reports

Abstract: Background: Massive gastrointestinal bleeding in children is uncommon. Dieulafoy lesion is an uncommon disease which may lead to massive and repeated upper gastrointestinal hemorrhage. We report two cases of gastric Dieulafoy lesion successfully treated with either band ligation or endoscopic hemoclipping. Case presentation: First case report: A previously healthy 18-month-old female infant with E. coli sepsis, pneumonia and respiratory failure with bilateral pneumothorax requiring chest drainage. Over a few d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…4 Endoscopic injection, hemostatic clamping, ligation, and electrocoagulation are all common treatments, but there are still risks of hemostatic failure or bleeding recurrence. 5,6 Due to rapid bleeding and poor visual field, hemostasis under endoscopy failed in our case. Selective angiography can be used as a second-line treatment for DL.…”
Section: Discussionmentioning
confidence: 73%
“…4 Endoscopic injection, hemostatic clamping, ligation, and electrocoagulation are all common treatments, but there are still risks of hemostatic failure or bleeding recurrence. 5,6 Due to rapid bleeding and poor visual field, hemostasis under endoscopy failed in our case. Selective angiography can be used as a second-line treatment for DL.…”
Section: Discussionmentioning
confidence: 73%
“…Surgery may ultimately be necessary if bleeding cannot be controlled. Di Nardo et al 7 studied pediatric cases of Dieulafoy’s lesions over the last 10 years and found hemostatic clipping to be successful in many cases. Many patients require multiple interventions due to a bleeding Dieulafoy’s lesions leading to complications and a prolonged hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Dieulafoy's disease occurs mostly in male adults and is rare in children. It is mostly sporadic and characterized by sudden, interstitial, and repeated bleeding ( 1 , 3 , 15 , 16 ). The incidence of Dieulafoy's disease in children has not been determined, and its causes are still unknown ( 3 , 16 ).…”
Section: Discussionmentioning
confidence: 99%